Lessons learned from building the kid’s trial with an online children’s and parents’ research advisory group: a descriptive, qualitative study - Lepage, Simone; Whelan, Barbara; Flight, Laura; Totton, Nikki; Devane, Declan (Research involvement and engagement, 2025)
Health research increasingly incorporates public and patient involvement (PPI) to enhance trial inclusivity and relevance, and it is often mandated by funding and regulatory bodies. PPI boosts public engagement with trials and aligns trial objectives more closely with the priorities of the groups they aim to benefit. The Kid’s Trial, an online randomised trial co-created with children, aims to help them better understand what randomised trials are, why they matter, and improve their critical thinking skills. To ensure inclusivity and relevance, we established two PPI groups: the Children’s Research Advisory Group (CRAG) and the Parents’ Research Advisory Group (PRAG). We recruited a representative sample of children and parents from diverse ethnic, geographic, and socioeconomic backgrounds to reflect the trial’s target demographic. We engaged PPI group members through social media and email campaigns aimed at parents of children aged 7 to 12. PPI meetings were conducted online, followed set agendas, and included real-time trial updates, post-meeting feedback surveys, and polls. A PPI compensation plan was established in advance. Online interviews later captured their insights and experiences as PPI partners. Seven family units, comprised of eight children and seven parents, were recruited over 15 weeks from six countries. PPI partners shaped the trial design by contributing to website animations, aesthetic changes, and language adaptations. Interviews were analysed using reflexive thematic analysis to explore the facilitators, challenges, and outcomes of participating in our online research advisory groups. Reflections from researchers and PPI partners demonstrated that participation in the advisory groups enhanced children’s learning and confidence. Many members, including children and adults, experienced unexpected positive outcomes, such as increased scientific literacy, science communication and confidence. Their involvement meaningfully shaped the trial’s development and processes. This study also provides guidance for researchers engaging similar demographics in future PPI activities. Plain English summary Health research now often includes input from the public and patients (Patient and Public Involvement or PPI) to make studies more inclusive and useful. Many funding and regulatory organisations require this. When the public is involved, research studies become more relevant to the people they aim to help. The Kid’s Trial is an online study designed with children to teach them how health research works and help them think critically about health information they encounter. To make sure The Kid’s Trial was inclusive and meaningful, we created two PPI groups made up of children and their parents to help us design it. We used social media and email to recruit a diverse group of children and parents from different backgrounds. These groups met online to discuss the trial, make improvements, and give feedback. They worked on the website, website animations, trial design, and the language we used. The PPI group members were compensated for their time. Seven family units, consisting of eight children and seven parents from six countries, joined the PPI groups. We interviewed group members to understand what worked well, what was challenging, and what they gained from participating in the PPI groups. Children felt that their confidence and learning had improved. Many PPI group members experienced unexpected benefits. Their input significantly influenced the design of The Kid’s Trial. This study also offers valuable advice for researchers seeking to include children and parents as PPI partners in future studies.